Audiences behind the Paywall: News Navigation among Established versus Newly Added Subscribers. Issue 3 (16th March 2021) - Wadbring, Ingela; Bergström, Lovisa
Abstract: How audiences behave behind newspaper paywalls is, in research, almost unknown territory. In editorial offices, however, this has become common knowledge, since traffic data is available around the clock. In this study, we have had the opportunity to study how subscribers with different degrees of subscription experience behave behind the paywall. In the analysis, we use traffic data generated from tracking scripts and stored in Amazon Redshift. The results are unambiguous. Readers with a paid subscription show a higher degree of activity, greater involvement, and more varied usage than do newly added readers with a free subscription, independent of age. Following subscribers with free subscriptions over time shows that their behaviour mainly is negative, with an overall lower degree of activity. Young subscribers with short-term accounts show the lowest degree of activity, independent of the measurement used. Implications of the results are discussed.